Prediction of Industrial Water Demand of Handan City Based on Water Saving Correction Value - XIA Feng; SUO Meiqin; WANG Yijie; WANG Lili (Renmin Zhujiang)
In order to accurately predict the industrial water demand of Handan City,based on the residual error correction GM(1,1) model and the equivalent dimensions addition,this paper proposes an equal-dimension-addition residual error correction GM(1,1) model to effectively predict the industrial water demand of each region in Handan city in 2025,as well as based on this,calculates the industrial water-saving correction value in 2025 according to the indicators of water consumption per ten thousand yuan of value-added by industry in Handan city issued by the Department of Water Resources of Hebei Province,and apply it to correct the predictive value.The results show that compared with the GM(1,1) model and residual error correction GM(1,1) model,the relative error of equal-dimension-addition residual error correction GM(1,1) model decreases by 33.9% and 12.5% respectively,and the relative error further reduces by 4.0% after the water saving correction value is used to correct the prediction results of the model,because of which it can be concluded that equal-dimension-addition residual error correction GM(1,1) model is more applicable for the prediction of industrial water demand in Handan City.Through the analysis of the calculation result from the equal-dimension-addition residual error correction GM(1,1) model and water saving correction value,the industrial water demand of Handan city in 2025 will be 34,799.90×104 m3,which would be helpful for the decision-making of the industrial sustainable development in Handan and also the prediction of water demand in other regions.